Management of Midshaft Clavicle Fractures in Adults. Issue 22 (15th November 2018) - Wiesel, Brent; Nagda, Sameer; Mehta, Samir; Churchill, Ryan
Abstract : Fractures of the clavicle are common injuries that occur across all age groups but are most frequently seen in the young, active patient population. Among the different types of clavicle fractures, those occurring in the middle third of the clavicular shaft are the most common. Historically, most of these fractures were treated by closed means even when notable displacement was present. Recently, there has been a renewed interest in assessing the best treatment option for these patients. Although nonsurgical treatment is a reliable method for treating many of these fractures, more recent data suggest that fractures with notable displacement (>2 cm of shortening or >100% displacement) and/or comminution have better short-term outcomes and lower rates of nonunion with surgical management. Current surgical options include superior plating, anterior-inferior plating, dual plating, and intramedullary nail fixation.